2022
DOI: 10.3390/molecules27072297
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical Potential in Kinetics Calculations on the HC3N + CN Reaction

Abstract: The reaction between the cyano radical CN and cyanoacetylene molecule HC3N is of great interest in different astronomical fields, from star-forming regions to planetary atmospheres. In this work, we present a new synergistic theoretical approach for the derivation of the rate coefficient for gas phase neutral-neutral reactions. Statistic RRKM calculations on the Potential Energy Surface are coupled with a semiempirical analysis of the initial bimolecular interaction. The value of the rate coefficient for the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…HC 3 N is a molecule with a recognized prebiotic potential (as many unsaturated nitriles), and therefore, within the framework of the Italian National Project of Astrobiology, we have recently investigated its reactions with other reactive radicals that are abundant in extraterrestrial environments where HC 3 N has been identified, such as N­( 2 D) (Titan and comets) and CN (also unpublished results) (Titan, interstellar clouds, and comets). This work is providing another piece in the puzzle of cyanoacetylene chemistry in space.…”
Section: Introductionmentioning
confidence: 99%
“…HC 3 N is a molecule with a recognized prebiotic potential (as many unsaturated nitriles), and therefore, within the framework of the Italian National Project of Astrobiology, we have recently investigated its reactions with other reactive radicals that are abundant in extraterrestrial environments where HC 3 N has been identified, such as N­( 2 D) (Titan and comets) and CN (also unpublished results) (Titan, interstellar clouds, and comets). This work is providing another piece in the puzzle of cyanoacetylene chemistry in space.…”
Section: Introductionmentioning
confidence: 99%